Green Mobility and Well-Being - Lucía Echeverría; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2021)
Recent years have witnessed efforts worldwide to promote green mobility, aimed at boosting sustainable economic growth. However, how green mobility relates to travelers' well-being remains an open question. We explore whether "green" modes of transportation (public transit and walking/cycling) are associated with higher levels of well-being in comparison to private driving, placing special focus on different types of travel (related to paid work, unpaid work, personal care, childcare, and leisure). We use the UK Time Use Survey (UKTUS) from 2014-2015, and exploit information on self-reported enjoyment during travel, as a measure of experienced well-being. We estimate Ordinary Least Squares and Random Effects regressions for each travel category, and find relative, positive effects of physical transport on enjoyment, in terms of personal care and leisure, while the relative negative effects of public transport are observed for childcare and work/paid travel, in relationship to traditional driving modes. Our evidence suggests a need to develop strategies to effectively promote mobility by physical modes, while improving the experience of public transit users.
Keywords: R4; J22; 330; subjective well-being; green travelling; walking/cycling; public transport